Bringing social context into global biomedical HIV cure-related research: An urgent call to action - Annie Miall; Rio McLellan; Krista Dong; Thumbi Ndung'u; Parya Saberi; John A. Sauceda; Karine Dubé (Elsevier, 2022)
Advances in science have ushered in a wave of new potential curative and control strategies for HIV that could eliminate the current requirement for life-long antiretroviral therapy (ART) for people living with HIV (PLWH). In this article, we argue that it is critical to consider social contexts in the development of HIV cure trial protocols. The biological and behavioral risk factors for HIV acquisition by study participants are inseparable from the social context in which these participants live. The article discusses an example of a cohort established to further HIV cure research that included social context, called the FRESH Acute HIV study, which combines a sociostructural intervention while conducting HIV prevention, treatment and cure-related research in Durban, South Africa. We make an urgent call to action to include sociobehavioral components as instrumental in future HIV cure trials in global context.